Pilot Project Land Degradation Neutrality (LDN), Namibia: Establishment of a baseline for land degradation in the region of Otjozondjupa - Nijbroek, Ravic P.; Mutua, John Y.; Soderstrom, Mats; Piikki, Kristin; Kempen, Bas; Hengari, Simeon (International Center for Tropical Agriculture, 2017)
Soil and vegetation data collected to develop LDN baselines in Otjozondjupa region of Namibia. The baselines include: land cover change, land productivity, soil organic carbon, and bush encroachment.